Treatment of iliac atherosclerotic lesions using the balloon-expandable dynamic bare metal stent: One-year outcomes of the BIODYNAMIC single-center retrospective analysis. (April 2021) - Torsello, Giovanni F; Doerr, Beatrix; Donas, Konstantinos; Berekoven, Bärbel; Torsello, Giovanni B; Beropoulis, Efthymios
Objectives: Endovascular therapy using balloon expandable stents has become the treatment standard for most iliac atherosclerotic lesions. We aimed to assess the safety and performance of the Dynamic stainless-steel balloon-expanding stent system in this location. Methods: BIODYNAMIC is a retrospective single center study including consecutive patients with iliac lesions treated with the Dynamic stent system. Not included were implantations inside an endograft. The primary endpoint was freedom from major adverse limb events (MALE) at 12 months, defined as index limb amputation or target lesion revascularization (TLR). Secondary endpoints were procedure success, ankle brachial index (ABI) and Rutherford class change, mortality and freedom from TLR after 12 months. Results: Within two years, 182 patients with 234 lesions in the common iliac artery were enrolled. Rutherford class 5 and 6 were present in 11.5% of patients, average stent diameter was 8.0 ± 0.5 mm and stented length 40.0 ± 15.3 mm. The primary endpoint was reached in 96.2% (225/234) of the cases, with six TLR (2.6%) and three target limb amputations (1.3%). Procedure success was obtained in all but three patients (98.4%). In paired analysis, ABI improved by 0.25 ± 0.21 from baseline to 0.90 ± 0.16 post-procedure and Rutherford class improved by −1.75 ± 1.53. There were four non-device–related deaths (2.2%). Freedom from TLR was 97%, 95.3%, 94% and 92.7% at 24, 36, 48 and 60 months, respectively. Conclusion: The Dynamic balloon-expandable stent system proved to be safe and effective in a population with common iliac artery lesions.